A simulation study to compare reference and other priors in the case of a standard univariate Student t-distribution - van der Merwe, A. J.; von Maltitz, M. J.; Meyer, J. H.; Groenewald, P. C. N. (South African Statistical Journal, 2022)
In this paper, reference and probability-matching priors are derived for the univariate Student t-distribution. These priors generally lead to procedures with properties frequentists can relate to while still retaining Bayes validity. The priors are tested by performing simulation studies. The focus is on the relative mean squared error from the posterior median and on the frequentist coverage of the 95% credibility intervals for a sample of size n = 30. Average interval lengths of the credibility intervals as well as the modes of the interval lengths based on 2 000 simulations are also considered. The performance of the priors is also tested on real data, namely daily logarithmic returns of IBM stocks.